Saving investment relationship with economic growth during financial crisis in Nigeria - Abu-Goodman, Maryam (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: The Global economic meltdown had called for a new model of managing and controlling of the banks and other financial institutions globally, after claiming thousands of jobs and over 120 banks across the world. This study aims to investigate the causal relationship between saving rates of Nigeria and real GDP growth especially over the period of 1980-2012 that includes the recent financial crisis. It is also the aim of the researcher to investigate the relationship between investment rate with real GDP growth during same period. Unlike previous studies, this study implements Johansen co-integration Estimation as well as Granger Causality analysis. In this analysis, the hypothesis of existence of any long-run equilibrium relationship between savings - investment function is tested by using Johansen co-integration method for Nigerian economy during economic crisis. The short-run dynamics are also captured from the vector error correction model. The estimates of the Johansen co-integration model suggest that there is a long run relationship between savings and investment. This result is consistent with a number of previous studies that found saving and investment to be co-integrated in the long run. Granger causality test result draws a conclusion that there is a unidirectional causal relationship from investment towards savings in Nigeria, where savings turns into consumption especially for imported commodities. Keywords: Savings, Investment, Gross Domestic Product (GDP). ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Küresel ekonomik kriz, global olarak, bankalarin ve finansal kurumların yonetım seklillerinde yeni modeller ortaya çıkarmıştır. Bu çalışma Nijerya’daki tassaruf oranı ve reel gayri safi yurtiçi hasıla (GDP) artış arasındaki nedensel ilişkiyi araştırmayı amaçlamıştır, 1980’ten 2012’ye, şimdiki krizi içine alarak. Bu calışma ile ayrıca yatırım oranları ve reel GDP artış arasındaki ilişkida aranmıştır, aynı zaman aralığında Diyer calışmalarda kinin aksine, bu calışmada Johansen co-integration ve Granger nedensellik testleri kullanılmıştır. Bu analizde, olası uzun vadeli equilibrium ilişkisi aranmıştır yatırım ve tasarruf arasında , Johansen co-integration test kullanılarak ekonomik kriz suresı boyunca. Johansen co-integration medeli göstermiştirki, yatırım ve tasarruf arasında uzun sureli ilişki vardır. Bu calışmadaki bulgu önceki calışmalardakilerle tutarlıdır. Granger nedensellik testinin sonucuna gore, Nijerya’da tek yönlü bir nedensellik ilişkisi mevcuttur, yatırımdan tasarrufa. Nijerya da tasarruflar tuketime döner, özellikle ithal ürünler için Keywords: Tasarruf, Yatırım, GDP.
Master of Science in Economics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2014. Supervisor: Assoc. Prof. Dr. Vedat Yorucu.
Keywords: Economics; Economic Conditions - Nigeria; National Income - Gross Domestic Product - Nigeria; Financial Crisis - Nigeria; Savings, Investment, Gross Domestic Product (GDP)